The Role of the Family in Improving the Character of Adolescents in Cilangkap Village, Buahdua District - Yuniati, Dhea; Lutfiansyach, Dadang Yunus (Learning Community : Jurnal Pendidikan Luar Sekolah, 2024)
Family is a social unit consisting of a father, mother and children. The family is the first and foremost educational forum in the child's life history which is an important basis in the formation of the human character itself. By using the observation method to dig up data in the field, the role of the family towards adolescents can be obtained where there are still teenagers who do not know the roles and functions of the family itself, even a small number of teenagers still feel uncomfortable and consider their families to be less harmonious. . The impact that will be caused is that the child will not feel comfortable and the child's mental health will be disturbed. Therefore, parents need to know how to prevent this from happening by emphasizing the function and role of the family itself.